ANTIKOLESTEROL PADA AYAM BOILER (Gallus domesticus) DARI BUNGA TELANG (Clitoria ternatea L) MELALUI METODE BIOTEKNOLOGI FERMENTASI KOMBUCHA: Anticolesterol In Boiler Chicken (Gallus Domesticus) From Telang Flower (Clitoria Ternatea L) Through Kombucha Fermentation Biotechnology Method - Yuliana Kolo, Firman Rezaldi, M.Fariz Fadillah, Desi Trisnawati, Barolym Tri Pamungkas, Aris Ma’ruf, (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2022)
Animal protein consumed in high amounts is one of the triggers for an increase in cholesterol levels. Cholesterol levels that tend to increase ideally can cause strokes, heart attacks, and death both at a young and old age. Telang flower produced through the biotechnology method of kombucha fermentation contains secondary metabolites both from alkaloids, flavonoids, and saponins as anticholesterol compounds. A broiler is one of the animal foods that have cholesterol. The purpose of this study was to produce broilers with low cholesterol. This study used 20 broilers at the age of 3 months and was treated with kombucha flower telang with different sugar concentrations. The design of this study was to use RAL (Completely Randomized Design) with 5 repetitions. The treatment consisted of T0 which is drinking water without a fermented kombucha solution of telang flower. T1 is drinking water which is added with a solution of 20% telang flower kombucha fermentation. T2 is drinking water that is added with a 30% telang flower kombucha fermentation solution. T3 is drinking water that is added to 40% telang flower kombucha fermentation solution. Cholesterol levels, body weight, and drinking water are the three test parameters carried out in this study. This study concludes that the concentration of white sugar by 40% in kombucha flower telang is the best substrate concentration lowering cholesterol levels in broilers.